Acute compartment syndrome of the hand in Henoch-Schonlein Purpura. - Luis, G.E.; Ng, E.S. (BioMed Central, 2007)
ABSTRACT: An eight year old boy with Henoch-Schonlein Purpura (HSP) presented with acute compartment syndrome (ACS) of his left hand following arterial cannulation of his radial artery in intensive care unit. Emergency decompression and fasciotomy were performed. The authors report this first case in literature and discuss how HSP can be complicated by ACS and ways to prevent the latter from happening.